2019
DOI: 10.1093/mnras/stz159
|View full text |Cite
|
Sign up to set email alerts
|

The origin of galactic metal-rich stellar halo components with highly eccentric orbits

Abstract: Using the astrometry from the ESA's Gaia mission, previous works have shown that the Milky Way stellar halo is dominated by metal-rich stars on highly eccentric orbits. To shed light on the nature of this prominent halo component, we have analysed 28 Galaxy analogues in the Auriga suite of cosmological hydrodynamics zoom-in simulations. Some three quarters of the Auriga galaxies contain prominent components with high radial velocity anisotropy, β > 0.6. However, only in one third of the hosts do the high-β sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 108 publications
17
138
0
Order By: Relevance
“…Please note that in the discussion above, instead of over-simplified "the last major merger", a more appropriate nomenclature perhaps would be "the last major that reached the Solar neighborhood". Interestingly, the end phases of the mergers as measured here match well those reported in Fattahi et al (2019): the differences are typically within 0.3 Gyr.…”
Section: Auriga Simulationssupporting
confidence: 84%
See 2 more Smart Citations
“…Please note that in the discussion above, instead of over-simplified "the last major merger", a more appropriate nomenclature perhaps would be "the last major that reached the Solar neighborhood". Interestingly, the end phases of the mergers as measured here match well those reported in Fattahi et al (2019): the differences are typically within 0.3 Gyr.…”
Section: Auriga Simulationssupporting
confidence: 84%
“…Figure 10 shows the behaviour of the azimuthal velocity as a function of metallicity (first and second column) and age (third and fourth column) for stellar particles in Auriga 6, 23 and 27. Note that these galaxies are amongst the ones with a highly radial stellar halo component as shown in Fattahi et al (2019). Moreover, Auriga 23 is the clearest example of the [α/Fe] bimodality as described in Grand et al (2018a).…”
Section: Auriga Simulationsmentioning
confidence: 82%
See 1 more Smart Citation
“…Efforts have been made to use hydrodynamical simulations to constrain the mass of the GES galaxy using metallicities and/or α-abundances to infer the mass of the accreted galaxies that contributed to the formation of the inner halo (Robertson et al 2005;Font et al 2006;Tissera et al 2013;Fattahi et al 2019;Mackereth et al 2018;Fernández-Alvar et al 2019;Vincenzo et al 2019). Our simulations support the notion that the chemical abundance patterns of the halo stars reflect the fact that a relatively massive accretion event occurred.…”
Section: Introductionsupporting
confidence: 60%
“…This Plume is largely responsible for the marked change in radial anisotropy with increasing [Fe/H] in the RRL sample, which resembles the one Belokurov et al (2018) found in a sample of main-sequence stars. In all respects, the kinematics of the Plume RRL closely resemble as the 'Gaia-Sausage' or 'Gaia-Enceladus' , which appear to have their origin in a large dwarf galaxy that merged with the MW (see also Myeong et al 2018;Kruijssen et al 2019;Mackereth et al 2019a;Vincenzo et al 2019;Fattahi et al 2019). The MDF of the Plume RRL is skewed towards higher metallicity than the MDF of other high-energy RRL, many of which are members of either the prograde Helmi-Stream or retrograde groups that may be part of the 'Sequoia' galaxy (Myeong et al 2019).…”
Section: Discussionmentioning
confidence: 90%